Porous electrode material, preparation method thereof and solid oxide fuel cell
The magnetron sputtering method is used to sputter electrode materials and pore-forming dielectric materials on the surface of the electrolyte substrate, which solves the problems of complicated and high-cost preparation process of porous electrode materials in the existing technology, and realizes efficient and controllable preparation of porous electrode materials. , improving the performance of solid oxide fuel cells.
Patent Information
- Application Number
- CN202411450104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art has complex processes and long cycles when preparing porous electrode materials, resulting in high overall costs and inability to accurately regulate the microstructure and pore distribution of electrode materials, which seriously restricts the development of solid oxide fuel cells.
The magnetron sputtering method is used to sputter electrode materials and pore-forming media materials on the surface of the electrolyte substrate. By adjusting the type and proportion of pore-forming media materials and the process parameters of magnetron sputtering, different pore sizes and pore structures can be obtained stably, quickly and efficiently. Porous electrode materials with regular distribution.
It simplifies the manufacturing process, shortens the preparation time, avoids the use of organic additives, is environmentally friendly, and is easy to produce on a large scale. It also obtains porous electrode materials with good performance and controllable pore structure, which improves the electrochemistry of solid oxide fuel cells. performance.
Smart Images

Figure CN119340402A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of porous electrode materials, and in particular to a porous electrode material and a preparation method thereof, and a solid oxide fuel cell. Background Art
[0002] A fuel cell is a new type of energy conversion device that can directly convert the chemical energy of a fuel into electrical energy under the action of an electrochemical reaction. Fuel cells are not limited by the thermodynamic Carnot cycle. As a branch of the fuel cell field, solid oxide fuel cells (SOFCs) have the advantages of high efficiency and low emissions that other fuel cells have. In addition, due to their unique structure and working characteristics, they have the following advantages: (1) a wide range of fuels; (2) low material cost; (3) long service life; (4) high power generation efficiency; (5) high waste heat utilization value; and (6) flexible and convenient installation.
[0003] For the anode material of SOFC, it is first necessary to have high catalytic activity to enable the fuel to undergo electrochemical oxidation reaction, and at the same time, it is necessary to have high electronic conductivity to transfer electrons. Within the working range of SOFC, it is necessary to show high electronic conductivity and oxygen ion conductivity. Therefore, there needs to be a certain porosity in the anode structure to ensure that the fuel gas can pass smoothly to participate in the electrochemical reaction, and to reduce the concentration polarization of the reaction and the contact resistance between the anode and the electrolyte. When SOFC is started, the anode needs to maintain good compatibility with other battery components within the range of room temperature to operating temperature, thermal matching with the electrolyte layer, and stability of morphology and structure.
[0004] For the cathode material of SOFC, porous cathode material can increase active sites and improve gas transmission efficiency, thereby improving the electrochemical performance of the battery.
[0005] At present, the preparation of porous anode materials or cathode materials mostly adopts methods such as tape casting, high temperature sintering, sol-gel method, sputtering, spraying and vapor deposition. The traditional preparation method of porous electrodes usually adopts the method of adding pore-forming agents into electrode slurry to form pores, but the method process is relatively complicated and will cause uneven pore size and non-straight pore size, thus affecting the performance of SOFC.
[0006] CN116799230A discloses a method for preparing a Ni-YSZ composite material, comprising mixing an anhydrous nickel source solution with a YSZ dispersion, reacting to obtain a powder under the action of a precipitant, and sintering the powder at a high temperature to obtain a Ni-YSZ composite material. The obtained composite material has a small particle size and a uniform particle size distribution.
[0007] CN116417647A discloses a method for preparing a nickel-based anode with finger-shaped holes for a solid oxide fuel cell. Nickel oxide powder and YSZ powder are mixed by wet grinding, dried and pre-sintered, and then ground and sieved to obtain a composite powder; polyvinyl pyrrolidone, polyether sulfone and N-methyl pyrrolidone are then mixed evenly, and the composite powder is added to prepare a nickel-based anode support casting slurry; and then the solid oxide fuel cell finger-shaped hole nickel-based anode is obtained through processes such as casting, curing, tableting and sintering.
[0008] However, the above methods for preparing SOFC porous electrode materials have the disadvantages of complex processes and long production cycles, resulting in high overall costs. In addition, the above processes can only prepare simple configurations and cannot accurately control the microstructure of the electrode material, especially the uniform distribution of pores, which seriously restricts the development of SOFC technology.
[0009] The magnetron sputtering coating process refers to a process in which particles (ions, atoms, molecules) with a certain energy bombard the solid surface under vacuum conditions, so that the atoms and molecules on the solid surface gain energy and escape from the solid surface. Through research, it is found that the film layer obtained by magnetron sputtering can form a porous film depending on the target material and sputtering conditions.
[0010] Therefore, how to effectively control the regular formation of porous electrode channels, and effectively control the number, distribution and pore size of the through holes, so as to improve the electrical performance of solid oxide fuel cells, has become a problem that needs to be solved urgently. Summary of the invention
[0011] In order to solve the above technical problems, the present invention provides a porous electrode material and a preparation method thereof, and a solid oxide fuel cell. The electrode material and a pore-forming medium material are sputtered on the surface of an electrolyte substrate by a magnetron sputtering method to form a porous electrode material. At the same time, by adjusting the type of pore-forming medium material, the ratio to the electrode material, and the process parameters of the magnetron sputtering, porous electrode materials with different pore sizes and pore structure distribution patterns that can meet various needs can be obtained stably, quickly and efficiently, thereby obtaining a solid oxide fuel cell with good performance and controllable pore structure.
[0012] To achieve this object, the present invention adopts the following technical solutions:
[0013] In a first aspect, the present invention provides a method for preparing a porous electrode material, the preparation method comprising the following steps:
[0014] Placing the electrode target material at a magnetron radio frequency sputtering target position, and placing the pore-forming medium target material at a magnetron direct current sputtering target position, or placing both the electrode target material and the pore-forming medium target material at a magnetron radio frequency sputtering target position, sputtering the electrode material and the pore-forming medium material on the surface of the electrolyte substrate by magnetron sputtering, and preparing a porous electrode material by heat treatment;
[0015] Wherein, the sputtering includes alternating sputtering or co-sputtering.
[0016] The present invention adopts magnetron sputtering to prepare electrode materials. By adjusting the type of pore-forming medium material, the ratio of pore-forming medium material to electrode material and the process parameters of magnetron sputtering, porous electrode materials with different pore diameters and pore structure distribution patterns can be obtained stably, quickly and efficiently, and can meet various needs. The manufacturing process of solid oxide fuel cells is simple and continuous, and the time consumption is greatly shortened. The entire preparation process does not use various organic additives, is environmentally friendly, and is easy to mass produce.
[0017] The present invention uses the electrode target material and the pore-forming medium target material as independent target materials, which makes it easy to adjust the addition ratio of the pore-forming medium material in the electrode film, and adjust the pore structure in the electrode material by adjusting the addition amount and pore-forming state of the pore-forming medium material.
[0018] In addition, the present invention has more controllable binding sites of the three-phase interface, and the sputtering rate of the target material of magnetron sputtering is highly controllable and accurate, and can be adjusted to the nanometer level. Compared with the pore-forming method of directly adding the pore-forming medium to the electrode target material, the present invention can flexibly adjust the content of the pore-forming medium and its position in the electrode, thereby easily obtaining a high power generation performance battery with uniform or special pore structure.
[0019] As a preferred technical solution of the present invention, the sputtering power of the electrode material is 100-450W, for example, 100W, 200W, 300W, 400W or 450W.
[0020] Preferably, the sputtering power of the pore-forming medium material is 50-300 W, for example, 50 W, 100 W, 150 W, 200 W, 250 W or 300 W.
[0021] Preferably, the sputtering power ratio of the electrode material to the pore-forming medium material is (1-10):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1.
[0022] Preferably, the sputtering power output mode of the magnetron sputtering method is any one of a direct current power supply, a radio frequency power supply, a medium frequency power supply or a pulse power supply, or a combination of at least two of them.
[0023] As a preferred technical solution of the present invention, if the sputtering is alternating sputtering, the sputtering time of the electrode material is 15 to 45 minutes, for example, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or 45 minutes, etc.; the sputtering time of the pore-forming medium material is 5 to 35 minutes, for example, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes or 35 minutes, etc.
[0024] Preferably, the number of times of alternating sputtering includes at least one.
[0025] Preferably, the total time of the alternating sputtering is 5 to 24 h, for example, 5 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h.
[0026] It should be noted that in the alternating sputtering, the electrode material is sputtered first, and then the pore-forming medium material is sputtered. This process is one alternating sputtering.
[0027] Preferably, after the alternating sputtering is completed, a process of sputtering a layer of electrode material is also included.
[0028] As a preferred technical solution of the present invention, the sputtering is co-sputtering, and the time of the co-sputtering is 2 to 10 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.
[0029] It should be noted that, in the co-sputtering, the sputtering of the electrode material and the sputtering of the pore-forming medium material are carried out simultaneously.
[0030] In the present invention, by adjusting the magnetron sputtering process and corresponding parameters, porous electrode materials with different pore diameters and pore structure distribution patterns can be obtained stably, quickly and efficiently, which can meet various needs.
[0031] As a preferred technical solution of the present invention, the temperature of the heat treatment is 800-1300°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C.
[0032] Preferably, the heat treatment time is 2 to 5 hours, such as 2 hours, 3 hours, 4 hours or 5 hours.
[0033] Preferably, the heat treatment is performed in an air atmosphere.
[0034] After magnetron sputtering, the electrode film material obtained in the present invention needs to be heat treated. During the sintering process, on the one hand, the pore former can be removed by high temperature to form a pore structure, and on the other hand, atoms can be migrated and reorganized to regulate bonding and change the structure to form a new stable crystal form.
[0035] As a preferred technical solution of the present invention, the distance between the electrode target and the electrolyte substrate is 5 to 10 cm, for example, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm.
[0036] Preferably, the distance between the pore-forming medium target and the electrolyte substrate is 5 to 10 cm, for example, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm.
[0037] Preferably, the electrolyte substrate has a thickness of 150 to 300 μm, for example, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, 280 μm or 300 μm.
[0038] Preferably, the total sputtering thickness of the electrode material is 0.5-5 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.
[0039] Preferably, the total sputtering thickness of the pore-forming medium material is 0.5-5 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.
[0040] Preferably, the electrolyte substrate comprises any one of metal, glass, polymer or ceramic material.
[0041] Preferably, the preparation method further comprises cleaning and drying the electrolyte substrate.
[0042] Preferably, the drying temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C.
[0043] Preferably, the drying time is 15 to 45 min, for example, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min or 45 min.
[0044] Preferably, the electrode material comprises an anode material or a cathode material.
[0045] Preferably, the anode material includes any one of NiO-yttria-stabilized zirconia, NiO-rare earth-doped yttria-stabilized zirconia or NiO, or a combination of at least two of them.
[0046] Preferably, in the NiO-yttria-stabilized zirconia, the mass ratio of NiO to yttria-stabilized zirconia is x:y, x+y=10, 5≤x≤7, for example, x may be 5, 5.5, 6, 6.5 or 7, etc.
[0047] Preferably, in the NiO-rare earth doped yttria stabilized zirconia, the mass ratio of NiO to rare earth doped yttria stabilized zirconia is a:b, a+b=10, 5≤a≤7, for example, a may be 5, 5.5, 6, 6.5 or 7, etc.
[0048] Preferably, the cathode material comprises any one of lanthanum strontium cobalt iron-yttria stabilized zirconia, lanthanum strontium cobalt iron-rare earth doped yttria stabilized zirconia, lanthanum strontium manganate-yttria stabilized zirconia or lanthanum strontium manganate-rare earth doped yttria stabilized zirconia or a combination of at least two thereof.
[0049] Preferably, the pore-forming medium material includes any one of graphite, zirconium-based materials or cerium-based materials, or a combination of at least two of them.
[0050] The preferred technical solution of the present invention is that before the sputtering, the process further comprises evacuating the vacuum to a degree of vacuum of 1.0×10 -5 ~8.0×10 -4 Pa, for example 1.0×10 -5 Pa, 3.0×10 -5 Pa, 5.0×10 -5 Pa, 8.0×10 -5 Pa, 1.0×10 -4 Pa, 3.0×10 - 4 Pa, 5.0×10 -4 Pa or 8.0×10 -4 Pa et al.
[0051] It should be noted that the vacuum degree mentioned in the present invention refers to the background vacuum.
[0052] Preferably, the sputtering is performed under a protective atmosphere.
[0053] Preferably, the protective atmosphere comprises argon or nitrogen, preferably argon.
[0054] Preferably, the flow rate of the protective atmosphere is 5 to 80 sccm, for example, 5 sccm, 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm or 80 sccm.
[0055] Preferably, the sputtering pressure is 0.5-2 Pa, for example, 0.5 Pa, 1 Pa, 1.5 Pa or 2 Pa.
[0056] Preferably, the sputtering temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C.
[0057] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0058] Placing an electrode target material at a magnetron radio frequency sputtering target position, placing a pore-forming medium target material at a magnetron direct current sputtering target position, sputtering an electrode material with a total thickness of 0.5 to 5 μm and a pore-forming medium material with a total thickness of 0.5 to 5 μm on the surface of an electrolyte substrate by a magnetron sputtering method, and heat treating at 800 to 1300° C. for 2 to 5 hours in an air atmosphere to prepare a porous electrode material;
[0059] wherein the sputtering power of the electrode material is 100 to 450 W; the sputtering power of the pore-forming medium material is 50 to 300 W; the sputtering power ratio of the electrode material to the pore-forming medium material is (1 to 10):1; the sputtering includes alternating sputtering or co-sputtering; the sputtering is alternating sputtering, the sputtering time of the electrode material is 20 to 40 min, and the sputtering time of the pore-forming medium material is 5 to 15 min; the number of alternating sputterings includes at least one; the total time of the alternating sputtering is 5 to 24 h; the sputtering is co-sputtering, and the co-sputtering time is 2 to 10 h; the distances between the electrode target material and the pore-forming medium target material and the substrate are each independently 5 to 10 cm; the thickness of the electrolyte substrate is 150 to 300 μm; the electrolyte substrate includes any one of metal, glass, polymer or ceramic material; the electrode material includes an anode material or a cathode material; The anode material comprises any one of NiO-yttria-stabilized zirconia, NiO-rare earth-doped yttria-stabilized zirconia or NiO, or a combination of at least two thereof; in the NiO-yttria-stabilized zirconia, the mass ratio of NiO to yttria-stabilized zirconia is x:y, x+y=10, 5≤x≤7; in the NiO-rare earth-doped yttria-stabilized zirconia, the mass ratio of NiO to rare earth-doped yttria-stabilized zirconia is a:b, a+b=1 0, 5≤a≤7; the cathode material includes any one of lanthanum strontium cobalt iron-yttria stabilized zirconia, lanthanum strontium cobalt iron-rare earth doped yttria stabilized zirconia, lanthanum strontium manganate-yttria stabilized zirconia or lanthanum strontium manganate-rare earth doped yttria stabilized zirconia or a combination of at least two of them; the pore-forming medium material includes any one of graphite, zirconium-based materials or cerium-based materials or a combination of at least two of them; before the sputtering, the process also includes evacuating the vacuum to a vacuum degree of 1.0×10 -5 ~8.0×10 -4 Pa; the sputtering is carried out under a protective atmosphere; the protective atmosphere includes argon or nitrogen; the flow rate of the protective atmosphere is 5 to 80 sccm; the sputtering pressure is 0.5 to 2 Pa; the sputtering temperature is 60 to 80°C; the preparation method also includes cleaning and drying the electrolyte substrate; the drying temperature is 60 to 80°C; the drying time is 15 to 45 min.
[0060] In a second aspect, the present invention further provides a porous electrode material, wherein the porous electrode material is prepared by the preparation method described in the first aspect.
[0061] In a third aspect, the present invention further provides a solid oxide fuel cell, which comprises the porous electrode material described in the second aspect.
[0062] Compared with the prior art, the present invention has at least the following beneficial effects:
[0063] 1) The present invention uses the electrode target material and the pore-forming medium target material as independent targets, so that the addition ratio of the pore-forming medium material in the electrode film can be easily adjusted, and the pore structure in the electrode material can be adjusted by adjusting the addition amount and pore-forming state of the pore-forming medium material;
[0064] 2) The present invention adopts magnetron sputtering to prepare electrode materials, which can stably, quickly and efficiently obtain porous electrode materials with different pore sizes and pore structure distribution patterns, and can meet various needs, making the manufacturing process of solid oxide fuel cells simple and continuous, and the time consumption is greatly shortened. The entire preparation process does not use various organic additives, is environmentally friendly, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is the XRD pattern of the anode material film prepared in Example 1 of the present invention;
[0066] Figure 2 This is a surface scanning electron microscope image of the anode material film prepared in Example 1 of the present invention;
[0067] Figure 3 This is a surface scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 1 of the present invention;
[0068] Figure 4 This is a cross-sectional scanning electron microscope image of the anode material film prepared in Example 1 of the present invention;
[0069] Figure 5 This is a cross-sectional scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 1 of the present invention;
[0070] Figure 6 This is a cross-sectional scanning electron microscope image of the anode material film prepared in Example 2 of the present invention;
[0071] Figure 7 This is a cross-sectional scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 2 of the present invention;
[0072] Figure 8This is an XRD comparison chart of the anode material film, the porous NiO-YSZ anode material prepared in Example 2 of the present invention, and the porous NiO-YSZ anode material prepared in Example 4. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0074] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0075] Example 1
[0076] This embodiment provides a method for preparing a porous anode material, the preparation method comprising the following steps:
[0077] NiO and YSZ powders were mixed evenly in a mass ratio of 6:4, and the mixed powder was pressed by a steel die to obtain an anode target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The anode target precursor was then placed in a hot pressing sintering furnace and sintered at 1500° C. for 12 h to obtain a NiO-YSZ target.
[0078] After the graphite is mixed evenly, it is pressed into a steel mold to obtain a pore-forming medium target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The pore-forming medium target precursor is then placed in a hot pressing sintering furnace for carbonization at 1000° C. and then heated to 2200° C. for graphitization sintering for 12 hours to obtain a pore-forming medium target.
[0079] The YSZ electrolyte substrate with a thickness of 200 μm was cleaned by ultrasonic ethanol for 15 min, and then dried in a forced air drying oven at 70 °C for 30 min.
[0080] The cleaned YSZ electrolyte substrate was placed on the coating sample stage of the magnetron sputtering instrument, the NiO-YSZ target was placed on the magnetron RF sputtering target position, and the pore-forming medium target was placed on the magnetron DC sputtering target position. The distance between the NiO-YSZ target and the pore-forming medium target and the electrolyte substrate was 8 cm. Then, the coating chamber and the sample chamber were evacuated to control the vacuum degree to 6.0×10 - 4 Pa, and then introduce argon into the coating chamber, control the flow rate of argon at 40sccm, and control the pressure at 0.6Pa;
[0081] Apply RF and DC sputtering power to start, set the RF sputtering output power to 450W, the DC sputtering output power to 250W, use the ion source current to clean the substrate for 15 minutes, then remove the baffles of the electrode target, the pore-forming medium target and the electrolyte substrate, and start sputtering coating on the surface of the electrolyte substrate. Sputter the RF power supply and the DC power supply alternately, first sputter (RF sputtering) NiO-YSZ, the sputtering power is 450W, the sputtering time is 30 minutes, and then sputter The graphite was sputtered (DC sputtering) at a power of 250 W and a sputtering time of 10 min. After alternating three times, a layer of NiO-YSZ was sputtered at a power of 450 W and a sputtering time of 30 min to obtain an anode material film, wherein the total sputtering thickness of NiO-YSZ was 0.5 μm and the total sputtering thickness of graphite was 0.5 μm. The film was placed in a muffle furnace and heat treated at 1000°C for 4 h under air conditions to obtain a porous NiO-YSZ anode material.
[0082] Figure 1 This is the XRD diagram of the anode material film prepared in Example 1. It can be seen from the figure that only YSZ exists in the anode material film, wherein NiO exists in an amorphous state.
[0083] Figure 2 This is a surface scanning electron microscope image of the anode material film prepared in Example 1. It can be seen from the image that the surface of the anode material film is dense.
[0084] Figure 3 This is a surface scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 1. It can be seen from the image that the surface of the porous NiO-YSZ anode material is loose and porous.
[0085] Figure 4 This is a scanning electron microscope image of the cross section of the anode material film prepared in Example 1. It can be seen from the image that the cross section of the anode material film has tight bonds between the layers and is dense within the layers.
[0086] Figure 5 This is a cross-sectional scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 1. It can be seen from the image that the pores of the porous NiO-YSZ anode material are evenly distributed, and the anode layer is tightly bonded to the electrolyte substrate.
[0087] Example 2
[0088] This embodiment provides a method for preparing a porous anode material, the preparation method comprising the following steps:
[0089] The NiO and YSZ powders were uniformly mixed in a mass ratio of 7:3, and the mixed powder was pressed by a steel mold to obtain an anode target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The anode target precursor was then sintered in a high-temperature furnace at 1400° C. for 16 h to obtain a NiO-YSZ target.
[0090] After the graphite is mixed evenly, it is pressed into a steel mold to obtain a pore-forming medium target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The pore-forming medium target precursor is then placed in a hot pressing sintering furnace for carbonization at 1000° C. and then heated to 2200° C. for graphitization sintering for 16 hours to obtain a pore-forming medium target.
[0091] The YSZ electrolyte substrate with a thickness of 150 μm was cleaned by ultrasonic ethanol for 30 min, and then dried in a forced air drying oven at 65 ° C for 15 min;
[0092] The cleaned YSZ electrolyte substrate was placed on the coating sample stage of the magnetron sputtering instrument, the NiO-YSZ target was placed on the magnetron RF sputtering target position, and the pore-forming medium target was placed on the magnetron DC sputtering target position. The distance between the NiO-YSZ target and the pore-forming medium target and the electrolyte substrate was 10 cm. Then, the coating chamber and the sample chamber were evacuated to control the vacuum degree to 8×10 - 4 Pa, and then introduce argon into the coating chamber, control the flow rate of argon at 30sccm, and control the pressure at 1.5Pa;
[0093] Apply RF and DC sputtering power to start, set the RF sputtering output power to 350 W, and the DC sputtering output power to 150 W, use the ion source current to clean the substrate for 15 minutes, then remove the baffles of the electrode target, the pore-forming medium target and the electrolyte substrate, and start sputtering coating on the surface of the electrolyte substrate. The RF power supply and the DC power supply are co-sputtered for 5 hours to obtain an anode material film, wherein the total sputtering thickness of NiO-YSZ is 0.5 μm, and the total sputtering thickness of graphite is 0.5 μm. Place it in a muffle furnace and heat treat it at 800°C for 5 hours under air conditions to obtain a porous NiO-YSZ anode material.
[0094] Figure 6 This is a cross-sectional scanning electron microscope image of the anode material film prepared in Example 2. It can be seen from the image that the anode material film layer is dense.
[0095] Figure 7 This is a cross-sectional scanning electron microscope image of the porous NiO-YSZ anode material prepared in Example 2. It can be seen from the image that the porous NiO-YSZ anode material is loose and porous.
[0096] Example 3
[0097] This embodiment provides a method for preparing a porous anode material, the preparation method comprising the following steps:
[0098] NiO and SYSZ (samarium-doped yttria-stabilized zirconia) powders were uniformly mixed in a mass ratio of 5:5, and the mixed powder was pressed by a steel mold to obtain an anode target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The anode target precursor was then sintered in a high-temperature furnace at 1600° C. for 8 h to obtain a NiO-SYSZ target.
[0099] The starch was mixed evenly and then pressed by a steel mold to obtain a pore-forming medium target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The pore-forming medium target precursor was then placed in a hot pressing sintering furnace for carbonization at 1000° C. and then heated to 2400° C. for graphitization sintering for 8 hours to obtain a pore-forming medium target.
[0100] The YSZ electrolyte substrate with a thickness of 300 μm was cleaned by ultrasonic cleaning with ethanol for 15 min, and then dried in a forced air drying oven at 80 ° C for 45 min;
[0101] The cleaned YSZ electrolyte substrate was placed on the coating sample stage of the magnetron sputtering instrument, the NiO-SYSZ target was placed on the magnetron RF sputtering target, and the pore-forming medium target was placed on the magnetron DC sputtering target. The distance between the NiO-SYSZ target and the pore-forming medium target and the electrolyte substrate was 5 cm. Then, the coating chamber and the sample chamber were evacuated to control the vacuum degree to 1.0×10 -5 Pa, and then introduce argon into the coating chamber, control the flow rate of argon at 80sccm, and control the pressure at 2Pa;
[0102] Apply RF and DC sputtering power to start, set the RF sputtering output power to 150 W, and the DC sputtering output power to 50 W, use the ion source current to clean the substrate for 15 minutes, then remove the baffles of the electrode target, the pore-forming medium target and the electrolyte substrate, and start sputtering coating on the surface of the electrolyte substrate. The RF power supply and the DC power supply are co-sputtered for 5 hours to obtain an anode material film, wherein the total sputtering thickness of NiO-SYSZ is 0.5 μm, and the total sputtering thickness of graphite is 0.5 μm. Place it in a muffle furnace and heat treat it at 1200°C for 2 hours under air conditions to obtain a porous NiO-SYSZ anode material.
[0103] Example 4
[0104] This embodiment provides a method for preparing a porous anode material. The difference between the preparation method and Example 2 is that the temperature of the heat treatment of the anode material film is adjusted to 1300° C., and the rest of the preparation method and parameters are consistent with Example 2.
[0105] Figure 8The XRD comparison diagrams of the anode material film prepared in Example 2, the porous NiO-YSZ anode material (heat treatment temperature 800°C) and the porous NiO-YSZ anode material prepared in Example 4 (the same as the anode material film prepared in Example 2, but the heat treatment temperature is adjusted to 1300°C) show that the crystal form of NiO can be changed after heat treatment, and there is an obvious NiO peak. As the heat treatment temperature increases, the crystallinity of NiO is higher and the crystal form is better.
[0106] Example 5
[0107] This embodiment provides a method for preparing a porous anode material. The difference between the preparation method and Example 2 is that the temperature of the heat treatment of the anode material film is adjusted to 1400° C., and the rest of the preparation method and parameters are consistent with Example 2.
[0108] Example 6
[0109] This embodiment provides a method for preparing a porous anode material. The difference between the preparation method and Example 2 is that the temperature of the heat treatment of the anode material film is adjusted to 700° C., and the rest of the preparation method and parameters are consistent with Example 2.
[0110] Example 7
[0111] This embodiment provides a method for preparing a porous anode material. The difference between the preparation method and Example 2 is that the RF sputtering output power is set to 350 W and the DC sputtering output power is set to 30 W. The other preparation methods and parameters are consistent with Example 2.
[0112] Example 8
[0113] This embodiment provides a method for preparing a porous anode material. The difference between the preparation method and Example 2 is that the RF sputtering output power is set to 350 W, the DC sputtering output power is set to 350 W, and the other preparation methods and parameters are consistent with Example 2.
[0114] Example 9
[0115] This embodiment provides a method for preparing a porous cathode material, the preparation method comprising the following steps:
[0116] The LSM (lanthanum strontium manganate) and YSZ (yttria stabilized zirconia) powders were mixed evenly in a mass ratio of 6:4, and the mixed powder was pressed by a steel mold to obtain a cathode target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The cathode target precursor was then placed in a hot pressing sintering furnace and sintered at 1200° C. for 12 hours to obtain an LSM-YSZ target.
[0117] After the graphite is mixed evenly, it is pressed into a steel mold to obtain a pore-forming medium target precursor with a diameter of 76.20 mm and a thickness of 5.60 mm. The pore-forming medium target precursor is then placed in a hot pressing sintering furnace for carbonization at 1000° C. and then heated to 2200° C. for graphitization sintering for 12 hours to obtain a pore-forming medium target.
[0118] The YSZ electrolyte substrate with a thickness of 200 μm was cleaned by ultrasonic ethanol for 15 min, and then dried in a forced air drying oven at 70 °C for 30 min.
[0119] The cleaned YSZ electrolyte substrate was placed on the coating sample stage of the magnetron sputtering instrument, the LSM-YSZ target was placed on the magnetron RF sputtering target position, and the pore-forming medium target was placed on the magnetron DC sputtering target position. The distance between the LSM-YSZ target and the pore-forming medium target and the electrolyte substrate was 10 cm. Then, the coating chamber and the sample chamber were evacuated to control the vacuum degree to 8.0×10 -4 Pa, and then introduce argon into the coating chamber, control the flow rate of argon at 50sccm, and control the pressure at 0.5Pa;
[0120] Apply RF and DC sputtering power to start, set the RF sputtering output power to 250W, the DC sputtering output power to 150W, use the ion source current to clean the substrate for 15 minutes, then remove the baffles of the electrode target, the pore-forming medium target and the electrolyte substrate, and start sputtering coating on the surface of the electrolyte substrate. Sputter the RF power supply and the DC power supply alternately, first sputter (RF sputtering) LSM-YSZ, the sputtering power is 250W, the sputtering time is 30 minutes, and then sputter The graphite was sputtered (DC sputtering) at a power of 150 W and a sputtering time of 10 min. After alternating three times, a layer of LSM-YSZ was sputtered at a power of 250 W and a sputtering time of 30 min to obtain a cathode material film, wherein the total sputtering thickness of LSM-YSZ was 0.5 μm, and the total sputtering thickness of graphite was 0.5 μm. The film was placed in a muffle furnace and heat treated at 1100°C for 4 h under air conditions to obtain a porous LSM-YSZ cathode material.
[0121] Comparative Example 1
[0122] This comparative example provides a method for preparing an anode material. The difference between the preparation method and Example 2 is that the pore-forming medium target material is omitted and only the NiO-YSZ target material is used. The rest of the preparation method and parameters are consistent with Example 2.
[0123] Application Examples 1 to 8 and Comparative Application Example 1
[0124] The porous anode materials prepared in Examples 1 to 8 of the present invention and the anode material prepared in Comparative Example 1 are respectively assembled into solid oxide fuel cells, corresponding to Application Examples 1 to 8 and Comparative Application Example 1, respectively.
[0125] Application Example 9
[0126] The porous cathode material prepared in Example 9 is assembled into a solid oxide fuel cell.
[0127] Test Method
[0128] 1) The solid oxide fuel cells of Application Examples 1 to 8 and Comparative Application Example 1 were reduced by introducing a nitrogen-hydrogen mixture for 2 h to reduce all the nickel oxide components therein to metallic nickel catalysts. Subsequently, their open circuit voltages and single cell output performances were tested under a hydrogen fuel atmosphere at 750°C. The specific test results are shown in Table 1.
[0129] 2) The open circuit voltage and single cell output performance of the solid oxide fuel cell of Application Example 9 were tested under a hydrogen fuel atmosphere at 750°C. The specific test results are shown in Table 1.
[0130] Table 1
[0131] project Open circuit voltage(V) <![CDATA[Power density (mW·cm -2 )]]> Application Example 1 1.107 57.325 Application Example 2 1.112 46.815 Application Example 3 1.162 43.114 Application Example 4 1.092 49.263 Application Example 5 1.106 23.274 Application Example 6 1.111 19.406 Application Example 7 1.109 24.117 Application Example 8 1.103 11.574 Application Example 9 1.024 43.561 Comparative application example 1 1.058 5.619
[0132] The test results show that:
[0133] (1) It can be seen from Application Examples 1 to 4 and Application Example 9 that the power density of the solid oxide fuel cell assembled with the porous electrode material prepared by the magnetron sputtering method of the present invention can reach 43 mW·cm -2 The above further shows that by using the magnetron sputtering method to sputter the electrode material and the pore-forming medium material onto the surface of the electrolyte substrate, the formation of porous electrode channels can be effectively controlled, and porous electrodes with many through holes that are orderly arranged and have larger pore sizes can be prepared, which facilitates the gas introduced into the electrode to be transmitted to the electrolyte surface for chemical reaction, thereby obtaining a solid oxide fuel cell with greater output power and better battery performance;
[0134] (2) It can be seen from Application Examples 5 and 6 that the heat treatment temperature of the anode material film of the present invention is 800-1300°C, which can make the NiO crystallinity higher and the crystal form better. It is applied to solid oxide fuel cells and has a higher power density. At the same time, it also avoids the warping of the anode material film and the phenomenon of loose bonding with the electrolyte substrate;
[0135] (3) It can be seen from Application Examples 7 and 8 that the sputtering power of the pore-forming medium material in the present invention is 50 to 300 W. Within this range, the pore size and distribution can be more accurately controlled, and the DC power supply and the RF power supply will not interfere with each other. The prepared electrode material is applied to solid oxide fuel cells and has a higher power density;
[0136] (4) By comparing with Application Example 1, it can be seen that the power density of the solid oxide fuel cell assembled with the anode material obtained by omitting the pore-forming medium target and only using the NiO-YSZ target is only 5.619 mW·cm -2 , because the pores in the anode material are significantly reduced, the reaction sites are significantly reduced, and the performance is significantly reduced.
[0137] In summary, the present invention utilizes magnetron sputtering to sputter electrode materials and pore-forming medium materials onto the surface of an electrolyte substrate to form a porous electrode material. At the same time, by adjusting the type of pore-forming medium material, the ratio to the electrode material, and the process parameters of magnetron sputtering, porous electrode materials with different pore sizes and pore structure distribution patterns can be obtained stably, quickly, and efficiently, and can meet a variety of needs, thereby obtaining a solid oxide fuel cell with good performance and controllable pore structure.
[0138] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a porous electrode material, characterized in that: The preparation method comprises the following steps: Placing the electrode target material at a magnetron radio frequency sputtering target position, and placing the pore-forming medium target material at a magnetron direct current sputtering target position, or placing both the electrode target material and the pore-forming medium target material at a magnetron radio frequency sputtering target position, sputtering the electrode material and the pore-forming medium material on the surface of the electrolyte substrate by magnetron sputtering, and preparing a porous electrode material by heat treatment; Wherein, the sputtering includes alternating sputtering or co-sputtering.
2. The preparation method according to claim 1, characterized in that: The sputtering power of the electrode material is 100 to 450 W; Preferably, the sputtering power of the pore-forming medium material is 50 to 300 W; Preferably, the sputtering power ratio of the electrode material to the pore-forming medium material is (1-10):
1.
3. The preparation method according to claim 1 or 2, characterized in that: The sputtering is alternate sputtering, the sputtering time of the electrode material is 15 to 45 minutes, and the sputtering time of the pore-forming medium material is 5 to 35 minutes; Preferably, the number of times of alternating sputtering includes at least one; Preferably, the total time of the alternating sputtering is 5 to 24 hours.
4. The preparation method according to claim 1 or 2, characterized in that: The sputtering is co-sputtering, and the co-sputtering time is 2 to 10 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the heat treatment is 800-1300°C; Preferably, the heat treatment time is 2 to 5 hours; Preferably, the heat treatment is performed in an air atmosphere.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The thickness of the electrolyte substrate is 150 to 300 μm; Preferably, the total sputtering thickness of the electrode material is 0.5 to 5 μm; Preferably, the total sputtering thickness of the pore-forming medium material is 0.5 to 5 μm; Preferably, the electrode material comprises an anode material or a cathode material; Preferably, the anode material comprises any one of NiO-yttria-stabilized zirconia, NiO-rare earth-doped yttria-stabilized zirconia or NiO, or a combination of at least two thereof; Preferably, the cathode material comprises any one of lanthanum strontium cobalt iron-yttria stabilized zirconia, lanthanum strontium cobalt iron-rare earth doped yttria stabilized zirconia, lanthanum strontium manganate-yttria stabilized zirconia or lanthanum strontium manganate-rare earth doped yttria stabilized zirconia or a combination of at least two thereof; Preferably, the pore-forming medium material includes any one of graphite, zirconium-based materials or cerium-based materials, or a combination of at least two of them.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Before the sputtering, the process also includes evacuating the vacuum to a degree of vacuum of 1.0×10 -5 ~8.0×10 -4 Pa; Preferably, the sputtering is performed under a protective atmosphere; Preferably, the protective atmosphere comprises argon or nitrogen, preferably argon; Preferably, the flow rate of the protective atmosphere is 5 to 80 sccm; Preferably, the sputtering pressure is 0.5-5 Pa; Preferably, the sputtering temperature is 60-80°C.
8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: Placing an electrode target material at a magnetron radio frequency sputtering target position, placing a pore-forming medium target material at a magnetron direct current sputtering target position, sputtering an electrode material with a total thickness of 0.5 to 5 μm and a pore-forming medium material with a total thickness of 0.5 to 5 μm on the surface of an electrolyte substrate by a magnetron sputtering method, and heat treating at 800 to 1300° C. for 2 to 5 hours in an air atmosphere to prepare a porous electrode material; wherein the sputtering power of the electrode material is 100 to 450 W; the sputtering power of the pore-forming medium material is 50 to 300 W; the sputtering power ratio of the electrode material to the pore-forming medium material is (1 to 10):1; the sputtering includes alternating sputtering or co-sputtering; the sputtering is alternating sputtering, the sputtering time of the electrode material is 20 to 40 min, and the sputtering time of the pore-forming medium material is 5 to 15 min; the number of alternating sputterings includes at least one; the total time of the alternating sputtering is 5 to 24 h; the sputtering is co-sputtering, and the co-sputtering time is 2 to 10 h; the distances between the electrode target material and the pore-forming medium target material and the substrate are each independently 5 to 10 cm; the thickness of the electrolyte substrate is 150 to 300 μm; the electrolyte substrate includes any one of metal, glass, polymer or ceramic material; the electrode material includes an anode material or a cathode material; The anode material comprises any one of NiO-yttria-stabilized zirconia, NiO-rare earth-doped yttria-stabilized zirconia or NiO, or a combination of at least two thereof; in the NiO-yttria-stabilized zirconia, the mass ratio of NiO to yttria-stabilized zirconia is x:y, x+y=10, 5≤x≤7; in the NiO-rare earth-doped yttria-stabilized zirconia, the mass ratio of NiO to rare earth-doped yttria-stabilized zirconia is a:b, a+b=1 0, 5≤a≤7; the cathode material includes any one of lanthanum strontium cobalt iron-yttria stabilized zirconia, lanthanum strontium cobalt iron-rare earth doped yttria stabilized zirconia, lanthanum strontium manganate-yttria stabilized zirconia or lanthanum strontium manganate-rare earth doped yttria stabilized zirconia or a combination of at least two of them; the pore-forming medium material includes any one of graphite, zirconium-based materials or cerium-based materials or a combination of at least two of them; before the sputtering, the process also includes evacuating the vacuum to a vacuum degree of 1.0×10 -5 ~8.0×10 -4 Pa; the sputtering is carried out under a protective atmosphere; the protective atmosphere includes argon or nitrogen; the flow rate of the protective atmosphere is 5 to 80 sccm; the sputtering pressure is 0.5 to 2 Pa; the sputtering temperature is 60 to 80°C; the preparation method also includes cleaning and drying the electrolyte substrate; the drying temperature is 60 to 80°C; the drying time is 15 to 45 min.
9. A porous electrode material, characterized in that: The porous electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A solid oxide fuel cell, characterized in that: The solid oxide fuel cell comprises the porous electrode material according to claim 9.